Android-Based Interactive Learning Media With Ethnophysics Approach To Improve Students Conceptual Understanding - Sefi Indah Lestari; Andik Purwanto; Rosane Medriati (Jurnal Penelitian Pembelajaran Fisika, 2025)
The purpose of this study is to describe the feasibility of android-based interactive learning media with an ethnophysical approach, describe the increase in students understanding of concepts, and describe students responses to android-based interactive learning media with an ethnophysical approach. The study was conducted in class XI C at SMAN 6 Bengkulu City in the 2024/2025 academic year. The method used is Research and Development using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Interviews, observations, and questionnaires were used in the study to collect data. Based on the product validity test, an average total validation of 80.20% was obtained, which met the criteria for being very suitable. The results of student responses through the response questionnaire to the media obtained an average score of 82.90%, with a very good category. The results of the N-Gain value through the pretest and posttest tests obtained a score of 0.68, which is included in the moderate classification. It can be concluded that developing android-based interactive learning media with an ethnophysical approach to parabolic motion material received a very good response.